Inflation in the early modern Ottoman Empire and Europe - YILDIRIM KARAMAN, SEÇİL (My University, 2022)
This study investigates the rates and causes of price inflation in early modern Europe and the Ottomans. There are two leading causes of price inflation in this period. The first is the American silver, and the second is the debasements that states resorted to for revenue. Our study shows that debasements are the more important cause. Debasements have induced price increases ranging between two to five hundred-fold for different states. As for American silver, it has induced, at most, a four-fold increase in prices. Hence inflation was mainly caused by debasements and the underlying political factors.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Social Sciences and Humanities; Economics; EKONOMİ; Ekonomi ve İş; Sosyal Bilimler (SOC); ECONOMICS; ECONOMICS & BUSINESS; Social Sciences (SOC); Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities; Price Revolution; Inflation; Debasement; Silver Standard; PRICE REVOLUTION; REAL WAGES; PERSPECTIVE; DIVERGENCE; HISTORY; TRADE; RISE